Penerapan Metode Reward dalam Pembentukan Disiplin Anak Usia 5-6 Tahun di RA Nurul Jannah Kecamatan Daha Utara - Asiah, Asiah; Jannah, Nor; Salhah, Salhah (Early Stage, 2025)
The purpose of this research is to find out how the application and constraints of the reward method in the formation of children's discipline at RA Nurul Jannah Hamayung Village, Daha Utara District. This type of research is field research. The approach used is a qualitative descriptive approach. The object of this research is the application of reward methods and constraints in forming 5-6-year-old children's discipline in RA Nurul Jannah Hamayung Village. The subjects in this study were teachers and head of RA Nurul Jannah and parents of children. Data were collected by observation, interview, and documentation. Data analysis was carried out by following the Miles Huberman interactive model with several stages: data collection, data reduction, data presentation, and conclusion drawing. The research results of the application of the reward method in disciplining children aged 5-6 years at RA Nurul Jannah Hamayung Village, Daha Utara District are by giving praise, giving applause, giving thumbs up, and giving material (stars and stationery), and the obstacles to the application of the reward method are psychological, physical, family, community and school conditions